Changes in the Erythrogram Parameters and in the Erythrocyte Sizes of Adult Pelophylax ridibundus (Pallas 1771) (Anura: Ranidae) Inhabiting the Sedimentation Lake of Brikel Thermal Power Plant in Southern Bulgaria - Zhivko Zhelev; Tihomir Vachev; Danail Minchev (Toxics)
Analyses of the hematological statuses of animals inhabiting areas of anthropogenic pollution may provide valuable insights into the extent of disturbance of their living conditions and the mechanisms of adaptation to various environmental stressors. The current work compares the erythrogram and erythrocyte-metric parameters of marsh frogs (Pelophylax ridibundus) inhabiting the polluted sedimentation lake of Brikel TPP in southern Bulgaria to those in frogs inhabiting a relatively clean habitat (reference population). The study includes a total of 120 individuals (30 females and 30 males from each site). For all of them, total erythrocyte count, hemoglobin concentration, hematocrit, MCV, MCH, and MCHC were evaluated via standard laboratory techniques. All erythrocyte metrics were determined microscopically in two blood smears from each animal. Our study reveals alterations in the erythrogram parameters and the erythrocyte sizes in marsh frogs living in conditions of chronic pollution with industrial wastewater compared to the animals from the reference site. The mean values for all erythrocyte morphology parameters are significantly lower in both female and male individuals inhabiting the polluted area compared to those originating from the reference one. Conversely, three erythrogram parameters—erythrocyte count, hemoglobin, and hematocrit—appeared significantly higher in females and males from the polluted site. The observed changes in the erythrogram parameters and erythrocyte sizes result from the deteriorated water quality of the sedimentation lake.